Japan and the Pacific Free Trade Area - Korhonen, Pekka, 1955- (Sheffield Centre for Japanese Studies/Routledge series., 1994)
Pekka Kormonen examines the nature of Japan's economic rise in relation to other nations in the Pacific area. With the P̀acific Century' nearly upon us, this work will be of interest to all those studying Pacific economies.